Wykorzystanie sieci Internet w biznesie - Drab-Kurowska, Anna (Using the internet in business, 2006)
Because of dynamic development in economy, the meaning of information grows up. The main goal of this article is to present the areas of activities of organizations in Internet. In the first part of the paper forms of organizations are considered. In the second part areas of activities of organizations are shown.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 175-186